2017
DOI: 10.3390/molecules22071176
|View full text |Cite
|
Sign up to set email alerts
|

The Exact Nuclear Overhauser Enhancement: Recent Advances

Abstract: Although often depicted as rigid structures, proteins are highly dynamic systems, whose motions are essential to their functions. Despite this, it is difficult to investigate protein dynamics due to the rapid timescale at which they sample their conformational space, leading most NMR-determined structures to represent only an averaged snapshot of the dynamic picture. While NMR relaxation measurements can help to determine local dynamics, it is difficult to detect translational or concerted motion, and only rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…When 3 J Hα–Hβ couplings were added into the calculation, the iterative protocol yielded 66 stereospecific assignments. Next, we converted Pin1 conventional NOEs into eNOEs using our recently developed buildup series method to see if more precise distance restraints would impact the yield of stereospecific assignments [30]. Indeed, eNOEs were extremely helpful in defining rotameric states and bond angles, even without the 3 J Hα–Hβ couplings.…”
Section: Resultsmentioning
confidence: 99%
“…When 3 J Hα–Hβ couplings were added into the calculation, the iterative protocol yielded 66 stereospecific assignments. Next, we converted Pin1 conventional NOEs into eNOEs using our recently developed buildup series method to see if more precise distance restraints would impact the yield of stereospecific assignments [30]. Indeed, eNOEs were extremely helpful in defining rotameric states and bond angles, even without the 3 J Hα–Hβ couplings.…”
Section: Resultsmentioning
confidence: 99%
“…For dense eNOE networks (an exceptional case is shown in Figure ), multistate structures can be calculated in CYANA that allow visualization of spatial sampling. This is due to the averaged nature of eNOEs, and consequently, an atom that samples multiple points in space will produce eNOE distances to nearby atoms that are the r −6 averages of all the distances sampled. If a sufficient amount of eNOEs define such an atom, then the combined network contains information about all of the sampled substates.…”
Section: Step‐by‐step Guide For Extracting Enoesmentioning
confidence: 99%
“…In addition, we showed that eNOEs contain similar and complementary information to both J couplings and RDCs . So far, we have only used eNOEs to calculate multistate ensembles of proteins up to about 150 resides . Currently, we are testing new directions for the applications of eNOE methodology.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The distances are derived from exact measurements of the nuclear Overhauser enhancement (eNOE). [9][10][11] In our initial applications of the method, we used uniformly 13 C, 15 N-labeled samples to extract distances between all protons pairs. [12] However, diagonal peak overlap becomes an increasingly limiting factor for proteins larger than ca.…”
Section: Noe Measurement and Analysismentioning
confidence: 99%
“…It consists of the homodimeric homoheptamer α rings referred to as α 7 α 7 . The distances are derived from exact measurements of the nuclear Overhauser enhancement (eNOE) . In our initial applications of the method, we used uniformly 13 C, 15 N‐labeled samples to extract distances between all protons pairs .…”
Section: Introductionmentioning
confidence: 99%